2003
DOI: 10.1038/sj.gt.3301995
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two Gβγ-binding proteins – N-terminally truncated phosducin and β-adrenergic receptor kinase C terminus (βARKct) – in heart failure

Abstract: Myocardial overexpression of the C-terminus of b-adrenergic receptor kinase (bARKct) has been shown to result in a positive inotropic effect or an improvement of survival in heart failure. However, it is not clear whether this beneficial effect is mainly because of dominant-negative inhibition of bARK1, and a consecutive resensitization of b-adrenergic receptors (bAR), or rather due to inhibition of other Gbgmediated effects. In this study, we tested whether overexpression of N-terminally truncated phosducin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Thus, the beneficial effects of βARKct could be also due to its inhibition of G bg signaling. In fact, Li et al (2003) have recently shown that, in rabbits with rapid ventricular pacing-induced heart failure, phosducin (a known G bg subunit-binding protein) exerted very similar beneficial effects on heart failure progression as did βARKct, but phosducin did not restore β-AR responsiveness as did βARKct. Thus, it is still an open question whether β-AR blocker-induced decrease in the (in CHF increased) activity of cardiac GRK2 can exert beneficial effects in the failing heart without affecting G bg signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the beneficial effects of βARKct could be also due to its inhibition of G bg signaling. In fact, Li et al (2003) have recently shown that, in rabbits with rapid ventricular pacing-induced heart failure, phosducin (a known G bg subunit-binding protein) exerted very similar beneficial effects on heart failure progression as did βARKct, but phosducin did not restore β-AR responsiveness as did βARKct. Thus, it is still an open question whether β-AR blocker-induced decrease in the (in CHF increased) activity of cardiac GRK2 can exert beneficial effects in the failing heart without affecting G bg signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it might be also possible that the beneficial effects of βARKct might be due to its inhibition of G βγ -signaling. In fact, Li et al (66) have recently shown that in rabbits with rapid ventricular pacinginduced heart failure, phosducin (a known G βγ -subunit binding protein) exerted very similar beneficial effects on heart failure progression as did βARKct, but phosducin did not restore βAR responsiveness as did βARKct. Thus, it is still an open question whether or not beneficial effects of βARKct in heart failure models are due to inhibition of GRK2 or to inhibition of G βγ -signaling.…”
Section: Role Of Changes In G-protein-coupled Receptor Kinasesmentioning
confidence: 99%
“…More recently, gene transfer of the ␤ARK1ct has been compared with truncated phosducin, another GRK inhibitor (489). Both inhibitors bind to G␤␥ subunits, yet only ␤ARK-1 contributes to ␤-AR cycling and improves cAMP accumulation in myocytes from failing rabbit hearts (489).…”
Section: Cycling Of ␤-Arsmentioning
confidence: 99%